Preparation and characterization of impregnated magnetic particles on oil palm frond activated carbon for metal ions removal - Muzakkir Mohammad Zainol,; Nor Aishah Saidina Amin,; Mohd Asmadi, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The magnetic adsorbents i.e. oil palm frond-magnetic particles (OPF-MP) and oil palm frond activated carbon-magnetic particles (OPFAC-MP) have been prepared by impregnation of iron oxide via co-precipitation method. The magnetic adsorbents and their parent materials were characterized using Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM), Brunauer Emmett Teller (BET), Barrett, Joyner & Halenda (BJH) and t-plot method, x-ray diffraction (XRD) and also using vibrating sample magnetometry (VSM) to study their properties and surface chemistry. The activated carbon magnetic adsorbent confers high surface area of 700 m2/g with amorphous structure and magnetic properties of 2.76 emu/g. The OPF-MP and OPFAC-MP were then applied in adsorption study for ions removal of Pb(II), Zn(II) and Cu(II). OPFAC-MP has shown high removal efficiency of 100 % with adsorption capacity up to 15 mg/g of Pb(II), Zn(II) and Cu(II) ions compared to OPF-MP. In addition, the magnetic adsorbents were also compared with their parent materials to observe the effect of magnetic particles. Accordingly, the impregnation of magnetic particles enhances the metal ions adsorption comparing to their parent materials.